2003
DOI: 10.1161/01.cir.0000089092.61590.a8
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of Nitrate Tolerance and Oxidative Stress by an Angiotensin II Receptor Blocker in Patients With Coronary Spastic Angina

Abstract: Background-Nitrates are widely used to treat coronary artery disease, but their therapeutic value is compromised by the rapid development of tolerance. Recently, the renin-angiotensin system has been suggested to play an important role in the development of nitrate tolerance. Methods and Results-Sixty-four patients with coronary spastic angina were investigated to clarify the effect of angiotensin II type 1 receptor blocker (ARB) therapy on nitrate tolerance. Transdermal nitroglycerin (10 mg/d) and an ARB (can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…3,4) Recent studies have shown that mitochondrial aldehyde dehydrogenase (ALDH2) plays a central role in the development of nitrate tolerance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4) Recent studies have shown that mitochondrial aldehyde dehydrogenase (ALDH2) plays a central role in the development of nitrate tolerance.…”
Section: Discussionmentioning
confidence: 99%
“…He thus had a multivessel coronary spasm. To elucidate the possible role of nitrate tolerance in the genesis of the drug-resistant coronary spasm, the examination of brachial flow-mediated dilatation (FMD), an indicator of endothelial function, 4) as well as ECG monitoring were performed before and after GTN patch (20 mg/day) for 3 days. The attacks recurred and increased in frequency associated with decreased FMD on continuous GTN application ( Figure 1).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that angiotensin II stimulates the generation of vascular reactive oxygen species via NADH/NADPH oxidase activation (10) and that an angiotensin II type 1 receptor blocker (ARB), valsartan, improves endothelial vasomotor dysfunction through suppression of free radical production in a rabbit infarction model (11). In addition, we previously reported that an ARB, candesartan, attenuates nitrate tolerance in patients with CSA (12). Therefore i g u r e 1 .…”
Section: Coronary Spastic Angina (Csa) Is Well Treated With Calcium Amentioning
confidence: 99%
“…Development of tolerance is rarely a problem when nitroglycerin sublingual tablets are taken intermittently, either for relief of an acute symptom or for short-term prophylaxis before activities predictably associated with angina. Some studies have shown that angiotensin receptor blockers may prevent nitrate tolerance (Hirai et al, 2003). Patients can develop rebound symptoms after abruptly stopping nitrates.…”
Section: Adverse Effectsmentioning
confidence: 99%